Effects of simvastatin on immunoreaction and inflammation in rats with asthma by regulating NOTCH signaling pathway: Simvastatin in Rats with Asthma - Zhang, Xiaomeng; Qiao, Haixia; Li, Min; Bai, Guangliang (Cellular and Molecular Biology, 2023)
To investigate the effect of simvastatin on the immunoreaction and inflammation in rats with asthma through the NOTCH signaling pathway, a total of 36 Sprague-Dawley (SD) rats were enrolled and randomly divided into the normal group (n=12), model group (n=12) and simvastatin group (n=12). The rats in the normal group were fed normally, those in the model group were prepared into models of asthma, and those in the simvastatin group were prepared into models of asthma and intervened with simvastatin. Next, the morphology of airway tissues was observed via hematoxylin-eosin (HE) staining assay. Besides, immunohistochemistry was employed to determine the expression of interferon-γ (INF-γ), and the relative protein expression levels of NOTCH2 and NOTCH3 were measured by Western blotting (WB). Additionally, enzyme-linked immunosorbent assay (ELISA) and quantitative polymerase chain reaction (qPCR) assay were carried out to detect the content of interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) and the relative mRNA expression levels of INF-γ, IL-6 and TNF-α, respectively. HE staining results uncovered that the airway tissues displayed normal morphology in the normal group and disordered morphology and obvious inflammatory infiltration in the model group. In comparison with the model group, the simvastatin group exhibited significantly improved morphology of airway tissues. Based on immunohistochemistry, the average optical density of INF-γ positive expression was increased in the model group and simvastatin group compared with that in the normal group (P<0.05), and it was distinctly lower in the simvastatin group than that in the model group (P<0.05). The results of WB showed that compared with those in the normal group, the relative protein expression levels of NOTCH2 and NOTCH3 were elevated in model group and simvastatin group (P<0.05), whereas they were overtly reduced in simvastatin group compared with those in model group (P<0.05). It was found through ELISA that the model group and simvastatin group had raised content of IL-6 and TNF-α in comparison with the normal group (P<0.05), while the simvastatin group exhibited markedly decreased content of IL-6 and TNF-α in comparison with the model group (P<0.05). The results of qPCR revealed that the relative mRNA expression levels of INF-γ, IL-6 and TNF-α were distinctly up-regulated in the model group and simvastatin group compared with those in the normal group, displaying statistically significant differences (P<0.05), whereas they were markedly lowered in simvastatin group compared with those in the model group, showing statistically significant differences (P<0.05). Simvastatin represses the immunoreaction and inflammation in rats with asthma by down-regulating the NOTCH signaling pathway.